PENERAPAN ASESMEN BERBASIS QUIZIZZ PADA MATA PELAJARAN PAI - Mutammimul Hayati; Zulfani Sesmiarni; Rodi Rodi; Mira Susanti; Filtra Yeni (EDUCATIONAL JOURNAL : General and Specific Research, 2024)
This study aims to determine the effect of implementing Quizizz-based assessment on improving Islamic Religious Education (PAI) learning outcomes of students at SMPN 4, Payakumbuh District. The problem faced is the low PAI learning outcomes caused by the lack of interaction and motivation in reading test questions. As a solution, the researcher implemented a Quizizz-based assessment, an interactive quiz platform that allows students to be more active and motivated in participating in the evaluation. The approach used in this study is Classroom Action Research. Data were collected through learning outcome tests given before and after the implementation of Quizizz. The results of the study showed that the completeness of student learning outcomes in the pre-cycle before using Quizizz-based assessment was 51.72%. After using Quizizz, in cycle I the percentage of student learning outcomes reached 79.13%, in cycle II the learning outcomes increased to 82.75%. In cycle III the percentage of student learning reached 93.10%. The results of the analysis showed a significant increase in student learning outcomes after the implementation of Quizizz-based assessment. Therefore, the implementation of Quizizz-based assessment can be an effective alternative in improving the quality of Islamic Religious Education learning at SMPN 4, Payakumbuh District.